Challenges and Opportunities for Effective Cancer Immunotherapies - Kershaw, Michael; Slaney, Clare (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Anti-cancer immunotherapies have generated spectacular outcomes in the clinical environment and changed treatment schemes for cancer patients. Adoptive cell therapies (ACTs), including using autologous tumor-infiltrating lymphocytes and chimeric antigen receptor (CAR) T cells, and checkpoint blockades have emerged as the most effective treatments for certain cancers. The current challenge for cancer immunotherapies is that although some patients have benefited from the treatments, a number of cancers are resistant. The purpose of this Special Issue is to understand anti-cancer immunotherapy treatment resistance mechanisms and explore new options to provide opportunities for effective treatments.